Preliminary Study Review: Integration of Case-Based Learning and Interactive Flipbooks for Sharia Accounting Courses - Nanda, Hanjar Ikrima; Putri, Sheila Febriani; Mustofa, Muhammad Ifan Ali; Aninda, Fina (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid development of digital technology is a new challenge in the world of education, including in the field of sharia accounting. Islamic accounting courses pose challenges for students in public universities due to the dense content and unique requirements of Islamic economics. This study analyzes the need for digital learning media to support effective and timely learning of Islamic accounting. Subjects involved include lecturers and students in Indonesia, with data collected through questionnaires and interviews. The results indicate a demand for digital textbooks that facilitate self-study, covering Islamic transactions and financial reporting in one semester. These textbooks should include case studies that reflect real-world conditions and links to instructional videos to enhance understanding of Islamic financial transactions and reporting.